Analysis of airport configuration and passenger behaviour - Kalakou, S.; Moura, F.; Medeiros, V. (SSS10, 10th International Space Syntax Symposium : proceedings of the 10th International Space Syntax Symposium, 2015)
Airports serve a variety of services related to both the preparation of the passengers for their air trip and their free time inside the terminal. Hence, the process of airport planning is complex and strongly case-specific because of the big variety of services that airports might offer. Based on these premises, this paper aims at analysing airport space configuration, considering the Theory of the Social Logic of Space (space syntax). It is assumed that a morphological investigation can shed light on pedestrian movements and choices enabling planners to propose more pedestrian-friendly terminals. The study explores the positional relationships between the aeronautical (e.g. check-in and security) and non-aeronautical services (e.g. retail services, beverage areas and lounge), taking into consideration the Lisbon Portela international airport case (the departure floor, in the check-in area before the security control zone). Space syntax is applied to analyse and evaluate the building plan and its implications on passenger perceptions and choices. Visibility Graph Analysis is developed and the variables: visual connectivity, visual integration (global and local), intelligibility and synergy of the terminal are compared to assess airport planning and space allocation. The configurational findings are faced with a survey conducted to collect data on passenger perceptions and choices. The frequency of usage of the non-aeronautical areas is estimated and passenger characteristics related to their personal profile, travel choices and activities inside the building contribute to the assessment of the terminal configuration through the use of Discrete Choice Modelling. The major conclusion of this paper is that the attempt to include SS indicators in DCM was rewarding since the initial assumption that SS affects passenger choices was proved through the significance of the equivalent variables that were included in the developed model. It was shown that SS can stimulate passenger choices and favour alternatives that are more accessible or well-connected.